(3GdEcdjds - (3GdMSf Hf CMeO Hf jYbhH GdgeOGfj , GHf GdMGFc , CHh eMeO,J (B334 (3g` s
(3ChdgG (B:s
(3fHPg ef GdMQa GdKGef cJGH GdEcdjd ai PcQ bUhQ MejQ heOfgG s
(3BNQgG (B:s
(3adG JGef GdCjGe Ef cfJ YGbdG dHjHG ade jMPQ dgG eKd UGOb s
(3fSNI CNQi fHPg CNQi ef GdLRA GdKGef CjVkG hJTJed edNUGJ dgPG GdLRA hNGUI TYQ Ydbegs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B204 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B269s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B229 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B27 s
Keywords: (3GdJGQjNs